Sleeping and emotion disorders in women using hormonal replacement therapy - Wilczak, Maciej; Samulak, Dariusz; Mojs, Ewa; Michalska, Magdalena Monika; Ziarko, Michał (Menopause Review/Przegląd Menopauzalny, 2011)
Sleeping and emotion disorders, especially insomnia and sleep continuity disorders, are most severely felt and determine women’s everyday life. The research was aimed at assessing the dependence of the occurrence of sleeping and emotion disorders in women of perimenopausal age and the use of hormonal replacement therapy. Women of similar age not using hormonal replacement therapy constituted the reference group. 90 patients from gynaecological wards in the Wielkopolska region and hospital outpatient clinics participated in the research. The patients were between 15 and 80 years of age (M = 49.81; SD = 11.69). In the study standardized test methods of determined reliability and internal accuracy were used: Courtauld Emotional Control Scale (CECS), Epworth Sleepiness Scale, Athens Insomnia Scale, Stanford Sleepiness Scale, Beck Depression Inventory, Satisfaction With Life Scale, Multidimensional Self-Esteem Inventory. The results show lower intensity of insomnia in women using HRT than in women not using HRT. No statistically significant differences were observed between the two groups as far as two other insomnia indicators were concerned. Self-esteem was treated as a complex variable composed of eleven dimensions. Statistically significant differences were noted in respect of one dimension only, i.e. competences. Women using HRT notice that they have much more competences than women not using HRT.